Adhesion of Various Geopolymers Coatings on Metal Substrates - Mares, Jakub; Mamon, Filip; Jaskevic, Martin; Novotny, Jan (Manufacturing Technology Journal, 2023)
This article deals with adhesion of various alkali-activated metakaolin-based geopolymer coatings on structural steel 1.0038 (according to EN 10025-2). This steel alloy was chosen in order to analysis ad-hesion of prepared geopolymer coatings. Our samples were characterized by laser and SEM micros-copy and grid test was performed. Microscopy was performed to get knowledge about visible charac-terization and overall quality of prepared coatings. Based on previous research SEM results corre-spond with properties changes in coatings and their classification of grid test. Grid test was per-formed and results was evaluated. These results show potential of our prepared GP and could be used as base for further research and possible application as anti corrosion coatings in construction or fire-resistant barriers. The aim of the research was to prepare alkali-activated metakaolin-based geopoly-mer on a structural steel substrate, to evaluate the visual quality of the coatings and to evaluate the results of the grid test.
Keywords: geopolymer; structural steel; microstructure; grid test; adhesion